Isovaline efficacy in a rat pup model of infantile spasms. Issue 1 (6th January 2021) - Manzoor, Rohaan; Malek, Farah; Malek, Sohail; Shin, Damian S.
Abstract : Infantile spasms, also known as epileptic spasms during infancy, is an epileptic disorder of infancy and early childhood that is associated with developmental delay or regression, high mortality rate and is difficult to treat with conventional antiseizure medication. Previously, we reported that a unique amino acid called isovaline had potent anticonvulsive efficacy in the 4-aminopyridine and pilocarpine rat models of seizures. In this study, we examined whether isovaline possess therapeutic utility in a well-established rat model of infantile spasms which involves the pretreatment of a pregnant dam with betamethasone and subsequent induction of spasms with N -methyl-D-asparate (NMDA), a glutamate receptor agonist, in 15-day old pups. We treated seven of these pups with saline prior to administering NMDA and eight of these pups with isovaline (300 mg/kg) intraperitoneal (i.p.) prior to NMDA. Isovaline significantly reduced the number of full-body jumps from 18.1 ± 5.0 to 6.3 ± 1.8 and leg/arm/tail strains from 4.4 ± 1.6 to 1.1 ± 0.5. A trend in a reduction of body twitch was noted in rat pups administered isovaline ( P  = 0.05), but no significant difference was seen in NMDA-induced head nods ( P  = 0.221). In conclusion, our data demonstrate a potential for isovaline to attenuate an aggressive form of epilepsy that typically requires highly toxic medications to treat in children.